INTRUDER DETECTION ROBOT USING LPC2148 - Ms. Y.Sharvani, Mrs.G.V.Pameela, Ms. E. Supriya (International Journal of Advanced Science and Technology, 2020)
Intruder Detection Robotis a virtual robot which can be useful majorly inMilitary where a proper care has to be taken so that no enemy can enter. As it is a risky attempt to keep an eye on the enemy by humans, we can use robots for that purpose which can accurately give the location of any intruder if detected. This can also be further developed using camera and remote to monitor and control the robot from a distant location. This paper mainly focuses on how accurately a human can be detected and appropriate measures can be taken within no time. It is developed using PIR sensor, GSM, GPS, LCD.